Analysis Study of “Food Cholesterol Detect” Application Development in Early Detection of High Cholesterol Food Consumption - Terati, Terati; Nazarena, Yunita; Sadiq, Ahmad (jitek, 2023)
The incidence of hypercholesterolemia in Indonesia is increasing daily, caused by a sinful lifestyle, lack of physical activity, and high consumption of foods high in fat. Patients with hypercholesterolemia have a cholesterol intake from food consumed by 46%. Related to these problems, we need a technology that can make it easier for people to manage the consumption of foods high in cholesterol by utilizing the sophistication of Smartphones. So researchers are interested in designing an application, "Food Cholesterol Detect", to detect early consumption of foods high in cholesterol. The system testing scenario is carried out using the system testing method of Black Box Testing. Trials on Users were conducted to assess the website-based Food Cholesterol Detect Application's appearance and the information presented. As for the test results, all of these website systems run well, and the test results on users, namely an average rating of 3-3.5 (good), and users feel helped by this application.